2021
DOI: 10.1007/s00423-020-02069-6
|View full text |Cite
|
Sign up to set email alerts
|

A detailed analysis of pediatric surgical malpractice claims in Germany: what is the probability of a pediatric surgeon to be accused or convicted?

Abstract: Aim of the study Pediatric surgeons treat a vulnerable population in which unfavorable outcome can lead to substantial long-term costs, placing them at risk for malpractice claims. This study aims to characterize the frequency and circumstances in which malpractice claims were successfully brought against pediatric surgeons in Germany over the last 5 years. Materials and methods Anonymous data on medical treatment errors and payments were acquired from the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 23 publications
0
2
0
1
Order By: Relevance
“…The risk of conviction for these litigations was found to be 2.27% per year for a paediatric surgeon. [ 10 ] Another study from the United States of America reported that 41% of total medico-legal cases were lodged against paediatric surgeons, making them most vulnerable to getting sued. [ 11 ]…”
Section: Discussionmentioning
confidence: 99%
“…The risk of conviction for these litigations was found to be 2.27% per year for a paediatric surgeon. [ 10 ] Another study from the United States of America reported that 41% of total medico-legal cases were lodged against paediatric surgeons, making them most vulnerable to getting sued. [ 11 ]…”
Section: Discussionmentioning
confidence: 99%
“…Appendicitis malpractice litigation is also a global problem. In Germany for example, pediatric appendicitis malpractice claims analysed over a 5 year period revealed that the most common reasons for conviction were surgical technical errors, and delayed diagnosis 27 . To decrease the risk of litigation, the authors recommend the objective and professional documentation of all interactions, to accept ones limits and seek help for unfamiliar cases, and to maintain transparent communication with parents and family members 27 .…”
Section: Garber)mentioning
confidence: 99%
“…Auch vor der Volljährigkeit werden die Schlichtungsstellen der Ärztekammern um ihre juristisch fundierten und gutachterlich basierten Empfehlungen gebeten, die Amts-und Landgerichte mit Behandlungsfehlervorwürfen beschäftigt und die medizinischen Dienste der Krankenkassen geben ihre Einschätzung ab. Somit ist die Begutachtung auch im Kindesalter ein Spiegel des Komplikationsspektrums und des Fehlermanagements und betrifft national und international in besonderer Weise die Frakturversorgung [3,6,11,12].…”
unclassified